Organic–Inorganic Hybridization Engineering of Polyperylenediimide Cathodes for Efficient Potassium Storage - Han, Pinyu; Liu, Fusheng; Zhang, Yamin; Wang, Yuyan; Qin, Guohui; Hou, Linrui; Yuan, Changzhou (Angewandte Chemie, 2021)
Polyperylenediimide (PDI) is always subject to its modest conductivities, limited reversible active sites and inferior stability for potassium storage. To address these issues, herein, we firstly propose an organic–inorganic hybrid (PDI@Fe‐Sn@N‐Ti3C2Tx), where Fe/Sn single atoms are bound to the N‐doped MXenes (N‐Ti3C2Tx) via the unsaturated Fe/Sn–N3 bonds, and functionalized with PDI via d–π hybridization, forming a high conjugated δ skeleton. The resulted hybrid cathode endowed with enhanced electronic/ionic conductivities, lowered dissociation barriers of multiple redox centers and a stable cathode electrolyte interphase layer displays a 14‐electron involved high‐rate capacities and long cycle life. Moreover, it shows competitive performance in full cells even under different folding states and low operating temperatures. Hierarchical organic–inorganic hybrid PDI@Fe‐Sn@N‐Ti3C2Tx is smartly designed and exhibits superb potassium‐storage properties, thanks to its unique properties including abundant contactable active sites, Fe/Sn–N3 bonds, electronic polarization, and strong coordination interactions, as shown by detailed experiments and theoretical calculations/simulations.